Generalized Joint Hypermobility, Muscle Strength and Physical Function in Healthy Adolescents and Young Adults - Scheper, Mark; de Vries, Janneke; Beelen, Anita; de Vos, Rien; Nollet, Frans; Engelbert, Raoul (Current Rheumatology Reviews, 2014)
Background: Generalized Joint Hypermobility (GJH) is regarded as the main diagnostic criterion for Hypermobility Syndrome and is assumed to be of importance for the development of musculoskeletal complaints and functional decline. However GJH is also highly prevalent amongst healthy individuals whereas its consequences for physical functioning are unclear. Therefore the objective of the study was to determine the association of GJH with physical functioning in healthy adolescents and young adults. Methods: 328 participants (mean age (sd): 20.2 (1.8), gender (male/female): 134/194) were included. In order to establish the effect of GJH, subjects with symptomatic forms of GJH were excluded, as were subjects with other conditions that could influence physical functioning. Age, gender, BMI, GJH, muscle strength and physical activity level (PAL) in METS were collected. Results: GJH was associated with reduced muscle strength for all muscle groups (p=<.05), controlled for age and BMI. Ranging from -0.7 to -1.0SD in females and -.3 to -1.3SD in males. GJH was found to be significantly associated with higher amounts of METS spent on cycling, ranging from +0.2 to +0.9SD in females (p=.002) and +0.3 to +0.9SD in males (p=.041), where lower amounts of METS spent on sports activities was observed, ranging from -0.4 to -1.2SD in females (p=.002) and -0.2 to -1.9SD in males (p=.004). Conclusion: Individuals with GJH have reduced muscle strength and tend to avoid dynamic activities and prefer more stable activities, like cycling. This may indicate that individuals with GJH adapt their behaviour to prevent musculoskeletal complaints and functional decline.
Keywords: young adults